General chemistry - Ebbing, Darrell D.; Gammon, Steven D. (Boston, MA, USA : Cengage Learning, 2017)
"The eleventh edition was carefully reviewed with an eye toward strengthening the content available in OWLv2, end-of-chapter questions, and updating the presentation. Nomenclature changes and the adoption of IUPAC periodic table conventions are highlights of the narrative revisions, along with changes to the discussion of d orbitals. In-text examples have been reformatted to facilitate learning, and the accompanying Interactive Examples in OWLv2 have been redesigned to better parallel the problem-solving approach in the narrative. New Capstone Problems have been added to a number of chapters."--
Chemistry and measurement -- Atoms, molecules, and ions -- Calculations with chemical formulas and equations -- Chemical reactions -- The gaseous state -- Thermochemistry -- Quantum theory of the atom -- Electron configurations and periodicity -- Ionic and covalent bonding -- Molecular geometry and chemical bonding theory -- States of matter; liquids and solids -- Solutions -- Rates of reaction -- Chemical equilibrium -- Acids and bases -- Acid-Base equilibria -- Solubility and complex-ion equilibria -- Thermodynamics and equilibrium -- Electrochemistry -- Nuclear chemistry -- Chemistry of the main-group elements -- The transition elements and coordination compounds -- Organic chemistry -- Polymer matherials: synthetic and biological.
Periodic table and conversion tables on lining papers.
Includes index.
Keywords: Chemistry -- Textbooks